2020
DOI: 10.1101/2020.08.22.20179697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control Strategies against COVID-19 in China: Significance of Effective Testing in the Long Run

Abstract: The coronavirus disease 2019 (COVID-19) outbreak is reasonably contained in China. In this paper, we evaluated the effectiveness of different containment strategies in halting the pandemic spread in both short- and long-term. We combined a networked metapopulation SEIR model featuring undocumented infections, actual mobility data and Bayesian inference to simulate the counterfactual outbreak scenarios removing each one or a combination of the following three policies in place: i) city lockdowns, ii) intercity… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…It revealed that people in developed countries and developing countries consider prices differently. Consistent with this observation, our study also found that people with a higher monthly income had a higher intention to use SARS-CoV-2 NAAT, [30][31][32] might make people relax their vigilance, so they might think that SARS-CoV-2 RAST is unnecessary.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It revealed that people in developed countries and developing countries consider prices differently. Consistent with this observation, our study also found that people with a higher monthly income had a higher intention to use SARS-CoV-2 NAAT, [30][31][32] might make people relax their vigilance, so they might think that SARS-CoV-2 RAST is unnecessary.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the different situations of the COVID‐19 pandemic in different countries might also change attitudes toward the SARS‐CoV‐2 RAST. The low risk of SARS‐Cov‐2 infection in China, because of strong interventions including quarantine, mask mandates, mass vaccination, and extensive NAAT, 30–32 might make people relax their vigilance, so they might think that SARS‐CoV‐2 RAST is unnecessary.…”
Section: Discussionmentioning
confidence: 99%